A meta-analysis of satisfaction in the banking sector. Issue 6 (5th September 2016) - Ladeira, Wagner Junior; Santini, Fernando De Oliveira; Sampaio, Cláudio Hoffmann; Perin, Marcelo Gattermann; Araújo, Clécio Falcão
Abstract : Purpose: The purpose of this paper is to present a systematic framework with a meta-analytical approach to distinguish various types of antecedents and consequences of satisfaction in the banking sector. Design/methodology/approach: The authors conducted searches in 13 databases and analysed 811 relationships in 210 articles. For the quantitative data analysis, the authors used the coefficient of correlation r as a metric variable to measure the effect size of the studied scope variables. Findings: The findings of this meta-analysis demonstrated ten dimensions that directly influence satisfaction in the banking sector: a bank's atmosphere, special treatment and relational benefits, timesaving features, the dimensions and determinants of service quality, customers' overall perceptions of service quality, end-user computing, service recovery, external factors, strategic orientation and behavioural outcomes. These ten dimensions were derived from 55 variables. Research limitations/implications: This meta-analysis reviewed relationships found worldwide in the literature, expanding and improving the current knowledge. It identified ways that research on satisfaction in the banking sector is lacking and presents suggestions for the elaboration of new studies to allow future researchers to better define their agendas. Practical implications: The results show that managers should care about satisfaction because it results from the consumer's banking experience. The ten dimensions affect satisfaction to differing degrees. Originality/value: This research tested the impact of the antecedents and consequences of satisfaction in the banking sector and presented important results through this meta-analytical review. This meta-analysis contributes to the marketing literature, with a set of empirical generalizations, including relationship coefficients and calculated fail-safe numbers.